REKONSTRUKSI EDUKASI DAN SOSIALISASI SECARA BERKELANJUTAN (RESISTAN) DALAM MEMPERINGATI HARI BUKU SEDUNIA - Franciscus Xaverius Wartoyo; Yuni Priskila Ginting (Bajang Institute, 2022)
This activity is in commemoration of World Book Day intending to promote the Reconstruction and Socialization of Continuing Education (RESISTAN). It is hoped that through socialization, the community can actively participate. The use of books to support academic activities will help students develop a scientific basis or strength for the information they receive. This activity uses a socialization model as a method of implementation. Education is the only way to develop quality human resources that can win the global competition. The type of research used in this research is field research with a sociological approach. Sources of data obtained in the form of primary data sources, namely the results of interviews, and secondary data sources in the form of all literature on the main topic of discussion. Data collection techniques in the form of field research through interviews and library research. The analysis method uses qualitative analysis and is described in an easy-to-understand way. This socialization develops skills in the context of educating the nation's life, intending to develop the potential of students to become human beings who believe and fear God Almighty, have a noble character, are healthy humans, and form a dignified national character and civilization, become citizens who are knowledgeable, competent, creative, independent, democratic, and responsible.